2009
DOI: 10.1111/j.1600-0404.1998.tb01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Saudi Arabia: experience from a university hospital

Abstract: Objectives ‐ To describe the pattern of presentation, the types of dementia and the associated conditions in Saudi patients. Materials and methods ‐Hospital‐based study using DSM‐IV and ICD 10 criteria for consensus diagnosis of cases from clinical information and results of investigations. Dementia subtypes were made according to NINCDS‐ADRDA, NINDS‐AIREN and ICD 10 criteria while CDR was used for severity grading. Results ‐ A total of 77 demented patients (49 males, 28 females) were studied. The hospital fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
2
19
1
Order By: Relevance
“…The prevalence of dementia in this study (12.9%) is similar to reported studies from Canada 8% [26], Italy 9.8% [27] and Netherlands 13.3% [28], but much higher than a previous hospital based study in Saudi Arabia 0.2% [12] and other countries. Farrag et al, 1998, [29] reported a prevalence of 4.5 % in As suit governorate-Egypt.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The prevalence of dementia in this study (12.9%) is similar to reported studies from Canada 8% [26], Italy 9.8% [27] and Netherlands 13.3% [28], but much higher than a previous hospital based study in Saudi Arabia 0.2% [12] and other countries. Farrag et al, 1998, [29] reported a prevalence of 4.5 % in As suit governorate-Egypt.…”
Section: Discussionsupporting
confidence: 78%
“…The patients' average age in our study was of the same range as most of the previous studies in Saudi Arabia [12], Brazil [32] and Malaysia [33]. A clear preponderance of males was also observed in the total sample and among patients with AD.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Subjects with dementia (29.6%) were higher than the ratio previously reported among older Saudis by Ogunniyi et al (1998) (2.1%). The higher prevalence may be because a larger proportion of the patients with organic mental disorders are being managed at the general hospital set up (i.e.…”
contrasting
confidence: 49%
“…Cognitive disorders and depression among older people have been studied (Ogunniyi et al, 1998) but other mental disorders in late life have received little attention.…”
mentioning
confidence: 99%